2018
DOI: 10.1111/rda.13210
|View full text |Cite
|
Sign up to set email alerts
|

Sequential medium with GH and IGF‐1 improved in vitro development of bovine preantral follicles enclosed in ovarian tissue

Abstract: The growth hormone (GH) and growth insulin-like factor-1 (IGF-1) act directly upon the regulation and growth in the different phases of preantral follicles. Thus, it is necessary to define their sequentiality until the in vitro preovulatory development. Therefore, the study aimed to assess the effects of a sequential medium containing GH and/or IGF-1 in the long-duration in vitro culture of preantral ovarian follicles. Ovarian fragments were cultivated: first half (days 1-7), second half (days 7-14) or during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…In this study, IGF-1 was found in oocytes and GCs of antral follicles, acting synergistically with FSH to stimulate oocyte growth, increasing the number of fully developed oocytes and increasing the immunoreactivity of the LH receptor in GCs (51). This effect of IGF-1 seems to be dependent on GH, at least in bovines (52). Data from studies in cultured human GCs indicate that GH stimulates the production of IGF-2, which suggest that IGF-2 may be also a mediator of GH effects in follicles acting through the receptor for IGF-1 (53).…”
Section: Ovarian Functioningmentioning
confidence: 99%
“…In this study, IGF-1 was found in oocytes and GCs of antral follicles, acting synergistically with FSH to stimulate oocyte growth, increasing the number of fully developed oocytes and increasing the immunoreactivity of the LH receptor in GCs (51). This effect of IGF-1 seems to be dependent on GH, at least in bovines (52). Data from studies in cultured human GCs indicate that GH stimulates the production of IGF-2, which suggest that IGF-2 may be also a mediator of GH effects in follicles acting through the receptor for IGF-1 (53).…”
Section: Ovarian Functioningmentioning
confidence: 99%
“…Treatment-T2 T2-TCM 199B-0-2; IGF-I-3-4; Cultured in TCM 199B for first 2 days (0-2)followed was able to restrict the need for growth factors during initial period of culture. Although it was reported that inclusion of IGF-I for the entire length of culture resulted in better proportion of M-II oocytes (Zhou and Zhang 2005;Arunakumari et al 2010,;Magalhães et al 2012;Luz et al 2013;Teja et al 2013;Costa et al 2014;Jimenez et al 2018), in this study culturing of PFs' in medium supplemented with IGF-I for first two days (T1; Table 2) showed increased proportion of oocytes reaching Metaphase-II which could be likely the direct action of IGF-I on its receptors in the oocytes and granulosa cells of follicles in the early stages of development (Walters et al 2006;Jee et al 2012;Magalhaes -Padilha et al 2012 andCosta et al 2014) or it is also possible that the effects of the presence of IGF-I during early culture period might have been carried forward into later stages of development. It is remarkable that the treatment which had increased the diameter of PFs' in culture (T1) was the one which supported higher meiotic maturation of oocytes subsequently (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Similar to liver, GH promotes IGF1 production in GCs [ 188 ] and enhances FSH action with increasing FSH receptor expression [ 189 ]. Sequential treatment with GH and IGF1, promotes in vitro follicular growth with normal parameters of viability and ultrastructure [ 190 ]. DHEA supplementation in women undergoing IVF increases IGF1 expression especially in poor responders [ 191 , 192 ].…”
Section: Role Of Intraovarian Paracrine and Endocrine Molecules In Fo...mentioning
confidence: 99%